Mini acceleration and deceleration driving strategy to increase the operational time of flywheel hybrid module - Abdul Manaf, Muhammad Zaidan; Fakeruddin, Shafarul Hafidi; Mohamad Shukri , Zakaria; Mohd Noor Asril, Saadun; Mohd Hafidzal, Mohd Hanafi (AIP Publishing LLC, 2014)
This paper presents a new driving strategy to increase the operational time of flywheel hybrid module. The flywheel hybrid module contains low cost mechanical parts which installed on the small motorcycle. Based on normal driving cycles characteristics, the Mini-AD driving strategy is develop. It is involved a series of short or mini acceleration cycle and short deceleration cycle on top of the normal driving cycles. The new strategy is simulated for flywheel hybrid module, aimed for acceleration phase only. Simulations show that the new driving strategy can increase the operational time of flywheel hybrid module up to 62.5%.